Bioassay-guided isolation of cytotoxic cycloartane triterpenoid glycosides from the traditionally used medicinal plant Leea Indica - Wong, Yau Hsiung; Kadir, Habsah Abdul; Ling, Sui Kiong (Hindawi, 2012)
Leea indica is a medicinal plant used traditionally to cure cancer. In this study, the cytotoxic compounds of L. indica were isolated using bioassay-guided approach. Two cycloartane triterpenoid glycosides, mollic acid arabinoside (MAA) and mollic acid xyloside (MAX), were firstly isolated from L. indica. They inhibited the growth of Ca Ski cervical cancer cells with IC(50) of 19.21 μM (MAA) and 33.33 μM (MAX). MRC5 normal cell line was used to calculate selectivity index. MAA and MAX were about 8 and 4 times more cytotoxic to Ca Ski cells compared to MRC5. The cytotoxicity of MAA was characterized by both cytostatic and cytocidal effects. MAA decreased the expression of proliferative cell nuclear antigen, increased sub-G1 cells, and arrested cells in S and G2/M phases. This study provides the evidence for the ethnomedicinal use of L. indica and paves the way for future mechanism studies on the anticancer effects of MAA.